Plasmablastic lymphoma presenting as a paravertebral mass in a patient with Crohn's disease after immunosuppressive therapy. Issue 1 (9th January 2007) - Redmond, M; Quinn, J; Murphy, P; Patchett, S; Leader, M
Abstract : The case of a 32-year-old man with a paravertebral mass and skin nodules, occurring against a background of immunosuppressive therapy for Crohn's disease, is presented. The tumours showed morphological and immunophenotypical features of plasmablastic lymphoma. To our knowledge, this is the first reported case of plasmablastic lymphoma presenting in this location, and also after immunosuppression with infliximab treatment for Crohn's disease.